Politica empresarial e suas repercussões na gerencia de imagem de uma organização gerida pelo governo: o caso da Empresa Brasileira de Correios e Telegrafos (ECT) - Migliaccio Filho, Rubens (1996)
Considering Business Policy as the major discipline directly linked to the general management of a company, the thesis presents an analysis modef in which Marketing is focused under a new perspective. It analyses the role of the State as an active component of the Business Policy, introduces the reader to the main concepts of the Strategor model created by the Centre HEC-ISA and examines the company's Image formation and management based on wider strategic orientation emphasizing market aspects. Using the previously established set of references, the author anafyses the Brazilian Enterprise of Posts and Telegraphs (ECT) through interviews and shared observations whit its most important strategists, describing how, in this specific case, the company's Business Policy affected the management of its Corporative Image.